“Pasar Bocah”: Penanaman Kecakapan Hidup Berwirausaha Anak Usia Dini - Wulansari, Suci (Pena Edukasia, 2023)
Indonesia is one of the ASEAN countries with the largest area and the most populous country. With the abundance of natural resources and human resources in Indonesia, then Indonesia should have the perfect capital for facing MEA 2015 The children's market activity is an activity that held at Hidayatullah Islamic Kindergarten in the context of companionship of life boundaries and entrepreneurship for children - early childhood, this is so that one day the child will be able to face it the challenges of different times and all millennial and on order of life that is fast paced, practical, logical and in we need an entrepreneurial spirit that we need to prepare early on In this activity, children are invited to design what needs just what has to be prepared in the children's market activity so that with this activity children can learn how to solve the current problem with Friends and children alike learn entrepreneurship on their own simple with fun.